Wireless networks in industrial environments: state of the art and issues - Carcelle, Xavier (2006)
Wireless is everywhere nowadays and WLAN (i.e. 802.11 standard family) has became used by almost any communications devices in the mass market. The recent achievements in the fields of modulation techniques, such as Spread Spectrum, coding methods, such as Turbocodes, CDMA2000, and frequencies allocation methods, such as OFDM and Frequency Hopping, has pushed the growing uses of reliable and low-cost wireless technologies. Among them the last standards are: IEEE 802.11 family (i.e. WiFi), HyperLAN and HyperLAN2, IEEE 802.15 (i.e. WPAN), IEEE 802.16 (i.e. WiMAX)… However, the industrial environments are not taken into consideration in the design of those standards, because its harsh constraints has specific characteristics (reliability, interferences with existing equipments, multi-path propagation, low-power consumption, real-time reconfiguration, security…) that need specific requirements and eventually standards. This paper will intent to give an overview of the wireless technologies and discusses the current and future possible technologies for the uses in the industrial environments (power plants and stations, factories, industrial buildings, automotive…). Our current works showed us that there is no perfect technology by it-self but the best trade-off solution is a hybrid architecture combining the right wired and wireless technologies.